2020
DOI: 10.20318/recs.2020.4815
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de contenido sobre prescripción enfermera en los medios de comunicación

Abstract: Introducción: los últimos avances sobre la prescripción enfermera suponen un importante reconocimiento para la profesión en España. Ante la falta de publicaciones sobre el enfoque del proceso por los medios de comunicación, surge esta revisión. Objetivo: conocer el abordaje periodístico del tema por los principales medios de comunicación españoles durante el año 2018. Metodología: estudio observacional, descriptivo. Se utilizó la base de datos MyNews, combinando una búsqueda general en todos los medios y otra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The authors in this study believe it is essential to enhance people’s awareness of nurse prescribing to win acceptance. Some suggested that social media campaigns can boost patient awareness of nurse prescribing and the social status of the nursing profession [ 24 ]. We firmly believe that nurses should prioritize developing their competencies before implementing nurse prescribing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in this study believe it is essential to enhance people’s awareness of nurse prescribing to win acceptance. Some suggested that social media campaigns can boost patient awareness of nurse prescribing and the social status of the nursing profession [ 24 ]. We firmly believe that nurses should prioritize developing their competencies before implementing nurse prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…When conducting interviews to gather feedback on nurse prescribing from medical professionals and the public, researchers may face difficulties obtaining honest opinions from them due to the fear of causing offense if negative attitudes and feelings are expressed. The internet has provided individuals with a public platform and anonymity, allowing them to express their feelings and thoughts [ 24 ]. Social media functions as virtual communities that allow the public to communicate about life-related topics.…”
Section: Introductionmentioning
confidence: 99%